2021
DOI: 10.1177/1971400921998972
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-induced transient circulatory arrest in transvenous embolization of cerebral arteriovenous malformations

Abstract: Due to advances in interventional techniques, the transvenous approach may present an effective treatment option for embolization of brain arteriovenous malformations (AVMs). Contrary to the transarterial method, the transvenous approach can only be utilized in a specific subset of patients and is not suitable as a standard procedure for all AVM lesions. While this technique can be helpful in certain patients, careful patient selection to ensure patient safety and favorable clinical outcomes is important. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For this reason, temporary flow arrest by either balloon occlusion or adenosine-induced circulatory arrest could facilitate and improve embolization [ 135 ]. Ghorbani et al tested the safety and efficacy of adenosine-induced circulatory arrest in the transvenous embolization of six patients with bAVMs and reported that at the 6-month follow-up, four patients had an mRS of 2 and two patients had an mRS of 1 [ 136 ]. Recently, Iosif et al described a novel approach to their previously reported transvenous method [ 137 ] that involved placing hypercompliant balloons intra-arterially for the selective occlusion of arterial feeders during ethylene vinyl copolymer (EVOH) transvenous injection [ 137 ].…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, temporary flow arrest by either balloon occlusion or adenosine-induced circulatory arrest could facilitate and improve embolization [ 135 ]. Ghorbani et al tested the safety and efficacy of adenosine-induced circulatory arrest in the transvenous embolization of six patients with bAVMs and reported that at the 6-month follow-up, four patients had an mRS of 2 and two patients had an mRS of 1 [ 136 ]. Recently, Iosif et al described a novel approach to their previously reported transvenous method [ 137 ] that involved placing hypercompliant balloons intra-arterially for the selective occlusion of arterial feeders during ethylene vinyl copolymer (EVOH) transvenous injection [ 137 ].…”
Section: Resultsmentioning
confidence: 99%
“…Endovascular approaches can assist with the treatment of AVMs through better visualization for operative or radiation planning, perioperative reduction of high-flow pedicles to make surgery safer or – in some cases, such as VOGMs – complete cure through embolization alone [ 1 , 55 , 62 ]. Innovation continues in this field, including transvenous access and embolization, flow modulation (in which cardiac output can be altered pharmacologically or via cardiac pacing to attempt safer delivery of embolic agents) and the use of single or multiple intravascular balloons to regulate flow during procedures [ 15 , 18 , 24 , 28 , 38 , 40 ]. These advances also come with risk, including injury to unaffected vessels during the procedure, off-target embolization, radiation exposure (especially important in smaller children/infants) and the risk of unexpected hemorrhage resulting from re-routing of blood flow post-embolization [ 4 ].…”
Section: Advances In Interventional Radiologymentioning
confidence: 99%
“…The original idea of Massoud et al of using compliant balloons in the main feeders to obtain temporary flow arrest and reduce intra-nidal pressure during TVE was successfully reported recently (84) and seems to be as effective as induced arterial hypotension. Alternatively, some authors advocate the use of adenosine-induced transient cardio-circulatory arrest for very high-flow bAVMs (85,86) to potentiate retrograde embolization during TVE and claim this to be safe in the few patients in which it was performed. Others, finally, advise employing rapid ventricular pacing reduce ventricular filling time (87).…”
Section: Accepted Manuscriptmentioning
confidence: 99%